2009
DOI: 10.1194/jlr.p800030-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Circulating oxidized LDL: determinants and association with brachial flow-mediated dilation

Abstract: Circulating oxidized LDL (oxLDL) levels are strongly correlated to LDL-cholesterol (LDL-c) and apolipoprotein-B100 (apoB100), making it difficult to disentangle their independent contributions to cardiovascular risk. We explored the determinants of oxLDL and the relation between oxLDL and flow-mediated dilation (FMD) of the brachial artery to investigate whether the oxLDL/LDL-c and oxLDL/apoB100 ratios are more informative than the separate variables. FMD of the brachial artery and plasma concentrations of oxL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 33 publications
6
28
3
2
Order By: Relevance
“…Using the same ELISA kit as our study, it has been reported that ox-LDL significantly correlates with LDL-cholesterol [34,41]. In our study, we were unable to show this association in any of our three groups.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Using the same ELISA kit as our study, it has been reported that ox-LDL significantly correlates with LDL-cholesterol [34,41]. In our study, we were unable to show this association in any of our three groups.…”
Section: Discussioncontrasting
confidence: 80%
“…It can be hypothesized that, alongside with the progression of the inflammatory status, ox-LDL increases with the chronicity of diabetes [33]. It was shown that ox-LDL is associated with hypercholesterolemia and high serum LDL-cholesterol [34,35]. Surprisingly, in our results, we found a significant increase in the ox-LDL level in parallel with a decrease in the LDL-cholesterol level in patients with prolonged diabetes.…”
Section: Discussioncontrasting
confidence: 64%
“…In our study, we found that HDL-c was a negative determinant of oxLDL, likes Navab et al [20] der Zwan et al [33]. There are several hypotheses about two possible mechanisms could contribute to the protective role of HDL in the formation of oxLDL [10,13,15,23]; they are related to two HDLassociated enzymes that have been shown to inhibit LDL lipid-peroxidation in vitro: Paraoxonase 1 [16] and platelet-activating factor acetylhydrolase [35], respectively.…”
Section: Discussionsupporting
confidence: 61%
“…16 Circulating plasma oxidized low-density lipoprotein (LDL) was determined by competitive enzyme-linked immunosorbent assay (Mercodia, Uppsala, Sweden). 17 Hemoglobin A1c (HbA1c) was analyzed by ion-exchange high-performance liquid chromatography (reference range, 4.3 to 6.1%) on a modular monitoring system (Bio-Rad, Veenendaal, The Netherlands). Glucose was measured enzymatically (Roche, Mannheim, Germany), and insulin was determined by a 2-site immunoradiometric assay (Medgenix Diagnostics, Fleurus, Belgium).…”
Section: Biochemical Analysesmentioning
confidence: 99%